Algebra 2 : with trigonometry ; application and connections ; solutions manual (Illinios : Glencoe/Macmillan/McGraw-Hill, 1992)
Mathematics and Statistics
Keywords: Algebra; Trigonometry; Equation; Linear relation; Matrices; Logarith; Statistics; Trigonometry